Crossover learning through a health campaign integrated in a bachelor of pharmacy curriculum - Norazrina Azmi,; Nor Syafinaz Yaakob,; Malina Jasamai,; Eng, Wee Chua (Penerbit Universiti Kebangsaan Malaysia, 2018)
Purpose: Continuous improvement in teaching and learning methods is vital for addressing the changing needs of pharmacy education. Many have agreed that one of the most effective approaches is crossover learning, whereby learners are actively involved in shaping their learning experiences and acquiring knowledge in both formal and informal settings. In this work, we report an ongoing initiative of facilitating a student-led health campaign, Brain Awareness Day, to promote crossover learning. Method: The campaign is included in our curriculum (Bachelor of Pharmacy with Honours) as a formal mode of learning and continuous assessment. A total of 84 pharmacy students were divided into groups of eight or nine to work on a drug addiction-themed assignment and present the result in the form of a poster exhibition. A short, online questionnaire was used to gather the students’ feedback on their learning experience and perceived gain of relevant insights from the campaign. Findings: Thirty nine out of 84 students took part in the survey. Most students agreed that their involvement in the campaign had contributed favourably to their learning experience and achievement of the pre-defined learning outcomes. The students also gave several suggestions for improving the organisation of the campaign. They suggested that more budget should be allocated for running the campaign, and that finding an off-campus venue might help to increase footfall. Significance: We concluded that the campaign had been effective in encouraging crossover learning, and it would remain an integrated sub-programme in our pharmacy curriculum. Diversifying methods of teaching and learning may help to realise Malaysia’s aim of developing well-rounded and employable graduates.